Performance of Cotton, Cotton-Polyester, and Polyester-Elastane Fabrics Impregnated with Ultrafine Polymeric Nanoparticles Loaded with Lavender Oil. (17th February 2021) - Saade, H.; de León-Gómez, R. Díaz; Treviño, M. E.; Rodríguez-Fernández, O. S.; Soriano-Corral, F.; Borjas, J. J.; Castellanos, F.; Enríquez-Medrano, F. J.; Valdez, J. A.; López, R. G.
Abstract : Lavender oil- (LO-) loaded ultrafine nanoparticles (NP) (diameter < 50   nm ) of a copolymer were used for impregnating fabrics of cotton, cotton polyester, and polyester-elastane. The copolymer was composed mainly of methyl methacrylate (MMA) units with a low proportion of methacrylic acid (MAA). Moreover, two kinds of NP were used: one containing uncrosslinked copolymer and another one composed of crosslinked material. All the fabrics impregnated with NP of uncrosslinked copolymer keep the aroma up to 25 washes. Under storage at ambient conditions, the fabrics impregnated with NP of either uncrosslinked or crosslinked copolymer emitted aroma for up to almost 60 days. The long duration of aroma emission from fabrics is attributed to ease of the small nanoparticles used in this study of penetrating and staying inside the pores of the fabric fibers.